2019
DOI: 10.3386/w26182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rural and Urban Hospital Closures on Inpatient Mortality

Abstract: This paper uses a difference-in-difference approach to examine the impact of California's hospital closures occurring from 1995-2011 on adjusted inpatient mortality for time-sensitive conditions: sepsis, stroke, asthma/chronic obstructive pulmonary disease (COPD) and acute myocardial infarction (AMI). Outcomes of admissions in hospital service areas (HSAs) with and without closure(s) are compared before and after the closure year. The paper focuses on: 1) the differential impacts of rural and urban closures, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 23 publications
3
77
0
1
Order By: Relevance
“…Given evidence that minor delays in care for certain conditions can lead to a significant increase in mortality, 14,16 closures of rural hospitals could lead to mortality increases in affected communities. 20 Because of the importance of timely response, EMS records are designed to include granular details on the nature of the service. For example, key events in a typical call include the following: (a) call arrives at dispatch (9-1-1), which then notifies the EMS unit (ambulance); (b) EMS arrives at scene; (c) EMS arrives at patient side; (d) EMS leaves the scene; (e) EMS arrives at destination; and (f) EMS returns to service.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Given evidence that minor delays in care for certain conditions can lead to a significant increase in mortality, 14,16 closures of rural hospitals could lead to mortality increases in affected communities. 20 Because of the importance of timely response, EMS records are designed to include granular details on the nature of the service. For example, key events in a typical call include the following: (a) call arrives at dispatch (9-1-1), which then notifies the EMS unit (ambulance); (b) EMS arrives at scene; (c) EMS arrives at patient side; (d) EMS leaves the scene; (e) EMS arrives at destination; and (f) EMS returns to service.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The average distance from a closed hospital to the next closest hospital in rural areas was 12 miles, which could lead to a considerable increase in time to care. Given evidence that minor delays in care for certain conditions can lead to a significant increase in mortality, closures of rural hospitals could lead to mortality increases in affected communities …”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, leads to overcrowding and stretched services, with worsening of patient outcomes, for resource-intensive services such as emergency medicine and obstetrics. 87,88 Two Harvard studies found that closure of rural hospitals resulted in a 3% rise in 30-day mortality for patients overall and a 5% rise in 1-year mortality for time-sensitive conditions; there was no evidence of any cost savings from closures. 89,90 These findings were mirrored in a study of hospital closures in California, which found an increase in overall mortality, with changes in mortality differing by diagnostic condition.…”
Section: The Unrecognised Problems Of Closurementioning
confidence: 99%
“…In Georgia alone, 7 rural hospitals have closed in the last 10 years, and 17 others are considered highly financially distressed and vulnerable to closure 2,3 . Hospital closures have a detrimental effect on the health and health‐seeking behavior of the population by decreasing access to care, 4 exacerbating dire economic conditions within communities, and worsening existing health disparities 5,6 …”
mentioning
confidence: 99%